Comparative Outcome Analysis of Penicillin-Based Versus Fluoroquinolone-Based Antibiotic Therapy for Community-Acquired Pneumonia: A Nationwide Population-Based Cohort Study. Issue 6 (February 2016) - Wang, Chi-Chuan; Lin, Chia-Hui; Lin, Kuan-Yin; Chuang, Yu-Chung; Sheng, Wang-Huei
Abstract : Abstract: Community-acquired pneumonia (CAP) is a common but potentially life-threatening condition, but limited information exists on the effectiveness of fluoroquinolones compared to β-lactams in outpatient settings. We aimed to compare the effectiveness and outcomes of penicillins versus respiratory fluoroquinolones for CAP at outpatient clinics. This was a claim-based retrospective cohort study. Patients aged 20 years or older with at least 1 new pneumonia treatment episode were included, and the index penicillin or respiratory fluoroquinolone therapies for a pneumonia episode were at least 5 days in duration. The 2 groups were matched by propensity scores. Cox proportional hazard models were used to compare the rates of hospitalizations/emergence service visits and 30-day mortality. A logistic model was used to compare the likelihood of treatment failure between the 2 groups. After propensity score matching, 2622 matched pairs were included in the final model. The likelihood of treatment failure of fluoroquinolone-based therapy was lower than that of penicillin-based therapy (adjusted odds ratio [AOR], 0.88; 95% confidence interval [95%CI], 0.77–0.99), but no differences were found in hospitalization/emergence service (ES) visits (adjusted hazard ratio [HR], 1.27; 95% CI, 0.92–1.74) and 30-day mortality (adjusted HR, 0.69; 95% CI, 0.30–1.62) between the 2 groups. The likelihood of treatment failure of fluoroquinolone-based therapy was lower than that of penicillin-based therapy for CAP on an outpatient clinic basis. However, this effect may be marginal. Further investigation into the comparative effectiveness of these 2 treatment options is warranted.